2020
DOI: 10.1053/j.gastro.2020.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids, But Not TNF Antagonists, Are Associated With Adverse COVID-19 Outcomes in Patients With Inflammatory Bowel Diseases: Results From an International Registry

Abstract: This article has an accompanying continuing medical education activity, also eligible for MOC credit, on page e12. Learning Objective: Upon completion of this CME activity, successful learners will be able to discuss how steroids are associated with severe outcomes from COVID-19 among patients with inflammatory bowel disease (IBD). See Covering the Cover synopsis on page 407. BACKGROUND AND AIMS: The impact of Coronavirus disease 2019 (COVID-19) on patients with inflammatory bowel disease (IBD) is unknown. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

55
816
14
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 656 publications
(905 citation statements)
references
References 25 publications
55
816
14
14
Order By: Relevance
“…85% of COVID-19 patients and 75% of hospitalized patients compared to 9% and 29% respectively in the study by Haberman et al (18). Our results are consistent with those of previous studies showing that the use of systemic corticosteroids is a risk factor for a severe course of COVID-19, particularly in inflammatory bowel diseases (19). None of the hospitalized patients was a daily smoker or ex-smoker, which is consistent with several studies finding a low proportion of smokers among patients with a moderate to severe outcome.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…85% of COVID-19 patients and 75% of hospitalized patients compared to 9% and 29% respectively in the study by Haberman et al (18). Our results are consistent with those of previous studies showing that the use of systemic corticosteroids is a risk factor for a severe course of COVID-19, particularly in inflammatory bowel diseases (19). None of the hospitalized patients was a daily smoker or ex-smoker, which is consistent with several studies finding a low proportion of smokers among patients with a moderate to severe outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Coronavirus disease (COVID- 19), mediated by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) is responsible for a major health crisis worldwide. COVID-19 can be complicated with a severe acute respiratory syndrome (ARDS) and multi-organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…ESR generally points to bacterial infection. We believed that intestinal ora being interrupted by SARS-COV-2 could not be excluded, as could be observed in other reports (22,23).…”
Section: Laboratory Examinations and Ct Scansmentioning
confidence: 79%
“…The study demonstrated a strong positive association between systemic corticosteroid use and increased mortality/ICU admission of COVID‐19 patients. The study also indicated that TNF antagonist, methotrexate, and IL‐12/23 inhibitors do not appear to be associated with severe COVID‐19 100 . We note that the effects of low‐dose dexamethasone against COVID‐19 are currently being evaluated in the RECOVERY trial 101 …”
Section: Introductionmentioning
confidence: 82%
“…Pooled data from 71 RCTs for steroids vs. no steroids found the relative risk of infections was increased by 60% (95% CI 30–90) for those receiving steroids (Table 4). 99 In a large cohort of patients with inflammatory bowel disease that was collected through an international registry, the outcomes of the use of high‐dose corticosteroids, among other immunosuppressives, in COVID‐19‐positive patients was evaluated 100 . The study demonstrated a strong positive association between systemic corticosteroid use and increased mortality/ICU admission of COVID‐19 patients.…”
Section: Introductionmentioning
confidence: 99%